A realist case study inquiry of English primary school physical activity initiatives. Issue 1 (2nd January 2023) - Defever, Emmanuel; Randall, Vicky; Jones, Michelle
ABSTRACT: Concern that children are not engaging in enough physical activity (PA) to bring about health benefits is a crisis globally. This paper aims to examine primary school-based PA initiatives from within an English context. A qualitative inquiry was adopted and underpinned by the socio-ecological model. The study was presented through a realist case study of three selected primary schools to reveal a collection of context-mechanism-outcome statements across five levels of the socio-ecological model (individual, interpersonal, institutional, community and policy). The findings highlighted a multi-layered interaction of PA within the school setting as well as the school's own relationships with external influences. Three key components emerged from the research findings; these included the (1) teacher's unintentional facilitation of simple PA in classroom settings, (2) innovative uses of community networks as an additional resource to schools and (3) the uncovering of a complexity of external influences from home, community and policies on school-based initiatives.